2017
DOI: 10.20398/jscr.v7i2.11437
|View full text |Cite
|
Sign up to set email alerts
|

Fios de sutura

Abstract: Purpose: This is a review with the aim of describing the physical and biological characteristics of the most used sutures in daily surgical practice, and their indications. Methods: We reviewed the medical literature by searching the Pubmed and SciElo databases. Results: Data on the ideal qualities of sutures, general classification, indications, uses criteria. The physical and biological characteristics of absorbable, nonabsorbable, monofilamentar and multifilamentar sutures were described. Conclusion: With t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 1 publication
1
7
0
6
Order By: Relevance
“…16 The three forms of PDO threads (mono, cog, and screw threads) are absorbed into the body over 6 months by hydrolysis and their rate of total loss of resistance occurs in approximately 63 days, which limits their clinical efficiency and long-term patient satisfaction. 17,18 On the other hand, PLA threads were developed after PDO threads. They are made from a biocompatible polymer derived from lactic acid.…”
Section: Discussionmentioning
confidence: 99%
“…16 The three forms of PDO threads (mono, cog, and screw threads) are absorbed into the body over 6 months by hydrolysis and their rate of total loss of resistance occurs in approximately 63 days, which limits their clinical efficiency and long-term patient satisfaction. 17,18 On the other hand, PLA threads were developed after PDO threads. They are made from a biocompatible polymer derived from lactic acid.…”
Section: Discussionmentioning
confidence: 99%
“…In PDO threads, biodegradation is caused by penetration of the fluids that break the molecules of the suture material. [7] Their rate of total loss of resistance occurs in about 63 days[89] and the degradation occurs by excision in the amorphous regions of the material. [10] Excision begins after 15 days and changes of the interfibrillar microstructure finally cause rupture of the thread, but in the present study, it was observed much earlier.…”
Section: Discussionmentioning
confidence: 99%
“…Both are synthetic and monofilament yarns; however, the polydioxanone yarn is absorbable by hydrolysis, with an absorption time of approximately 90-180 days, causing small inflammatory reaction when compared to other suture materials such as catgut and cotton. Polypropylene is inabsorbable and biologically inert, even in the presence of infection, with high chemical resistance to acids, alkalis and enzymes 12 .…”
Section: Introductionmentioning
confidence: 99%